Cellular enzyme-modulating activity of p-acetoxycinnamyl alcohol from Alpinia officinarum - Chang-Dae Lee; Hyosun Lim; Hak-Dong Lee; Sullim Lee; In Young Bae; Sanghyun Lee (Applied Biological Chemistry)
Abstract Alpinia officinarum, commonly referred to as lesser galangal, is a medicinal plant traditionally used in East Asian practices owing to its anti-inflammatory, antioxidant, and antimicrobial properties. This study aimed to isolate p-acetoxycinnamyl alcohol from A. officinarum and evaluate its effect on melanogenesis-related enzyme expression. p-Acetoxycinnamyl alcohol was successfully isolated and structurally characterized from A. officinarum using NMR spectroscopy. The compound’s skin-whitening potential was investigated through a combination of molecular docking simulations and in vitro assays using B16F10 melanoma cells. The results demonstrated that p-acetoxycinnamyl alcohol showed potent binding affinity and inhibited the expression of microphthalmia-associated transcription factor, tyrosinase, tyrosinase-related protein (TRP)-1, and TRP-2 in melanocytes as shown by molecular docking simulations and in vitro assays. These findings indicate that p-acetoxycinnamyl alcohol has potential as a natural skin-whitening compound that controls melanogenic enzyme expression and functionality. The therapeutic potential of A. officinarum in functional cosmeceuticals and dermatological therapies emphasizes its pharmacognostical importance.